2017
DOI: 10.1136/gutjnl-2017-314015
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of acute arterial events in young patients and severely active IBD: a nationwide French cohort study

Abstract: Patients with IBD are at increased risk of acute arterial events, with the highest risk in young patients. Disease activity may also have an independent impact on the risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
125
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 40 publications
4
125
1
5
Order By: Relevance
“…The present study was based on data from the French national hospital discharge database. The latter contains a large number of cases of CD (n = 129 089, ensuring high‐statistical power), and has already been analysed in epidemiological studies of IBD . With regard to CD, the discharge data were cross‐validated against the cumulative incidence found in the EPIMAD registry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was based on data from the French national hospital discharge database. The latter contains a large number of cases of CD (n = 129 089, ensuring high‐statistical power), and has already been analysed in epidemiological studies of IBD . With regard to CD, the discharge data were cross‐validated against the cumulative incidence found in the EPIMAD registry.…”
Section: Discussionmentioning
confidence: 99%
“…Patients having at least one in‐patient stay for CD between 1 January 2007 and 31 December 2014 were considered for eligibility in this study. Inpatient stays with CD were identified by searching the database with the following ICD‐10 diagnostic codes: K50.0, K50.1, K50.8 or K50.9 (“Crohn's disease [regional enteritis]”) . When patients had an ulcerative colitis (UC) code (K51*) during one in‐patient stay and a CD code during another, only individuals with a CD code during the last in‐patient stay (in our study period) were considered.…”
Section: Methodsmentioning
confidence: 99%
“…However, the association between chronic systemic inflammation and the risk of acute arterial events remains unclear in patients with IBD. Two studies based on medico-administrative databases concluded that IBD disease activity was an independent predictor of acute arterial events [5,6]. However, the disease activity was assessed trough indirect markers, including hospitalizations, surgical procedures, and treatment exposure [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Second, an algorithm was used to identify UC patients. Other studies have used the same algorithm, based on the combination of hospitalisation and long‐term diseases UC codes. The present study also used dispensing of infliximab (excluding other indications for anti‐TNF therapy).…”
Section: Discussionmentioning
confidence: 99%